Manganese Enhanced MRI for Use in Studying Neurodegenerative Diseases - Saar, Galit; Koretsky, Alan P. (Frontiers in Neural Circuits, 2019)
MRI has been extensively used in neurodegenerative disorders, such as Alzheimer’s disease, frontal-temporal dementia, mild cognitive impairment, Parkinson’s disease, Huntington’s disease and amyotrophic lateral sclerosis. MRI is important for monitoring the neurodegenerative components in other diseases such as epilepsy, stroke and multiple sclerosis. Manganese enhanced MRI (MEMRI) has been used in many preclinical studies to image anatomy and cytoarchitecture, to obtain functional information in areas of the brain and to study neuronal connections. This is due to Mn2+ ability to enter excitable cells through voltage gated calcium channels and be actively transported in an anterograde manner along axons and across synapses. The broad range of information obtained from MEMRI has led to the use of Mn2+ in many animal models of neurodegeneration which has supplied important insight into brain degeneration in preclinical studies. Here we provide a brief review of MEMRI use in neurodegenerative diseases and in diseases with neurodegenerative components in animal studies and discuss the potential translation of MEMRI to clinical use in the future.